Avaliação de estoques pesqueiros do reservatório de Itaipu por meio das abordagens uni-específica e ecossistêmica. - Philippsen, Juliana Strieder (2017)
The most important stocks of Itaipu reservoir were assessed through data-poor methods and ecosystem modeling. Data-poor methods are being tested, and applications in real situations still are scarce. The comparison of two data-poor methods (CMSY and COM-SIR) showed different conclusions about stock status, information which is very useful in fisheries management. Both methods rely on assumptions that do not always correspond to reality, thus it is necessary caution when management is based on this type of method, and when possible to adopt methods with different types of data (e.g. length), to complement the assessment. Length-based indicators showed a high proportion of juveniles in the landings, except for Prochilodus lineatus and Hypophthalmus edentatus. The results obtained with COM-SIR indicated high probability of overfishing for the stocks of P. lineatus, Plagioscion squamosissimus and Zungaro jahu. Ecological indicators showed that there are no expressive impacts due to fishing on the ecosystem. Keystone species identified in Itaipu reservoir (Salminus brasiliensis, Z. jahu, Serrasalmus spp., and Hoplias spp.), are also important for the local fishery, highlighting the necessity in managing them carefully, not only due their importance to the fishery but also for the ecological role they play. Simulations evidenced that increases in fishing effort will not result in expressively increases in catches, thus it is suggested that fishing effort do not increase in relation to effort observed in 2011.